Nanofiber ionic bridge framed quasi-solid polymer electrolyte with nanocellulose and PAF for improved low-temperature lithium battery - Jiayi Luo; Shenyuan Li; Yangyang Yu; Chengjun Song; Zhaoyan Sun; Baijun Liu; Wei Hu (Chemical Engineering Journal, 2026)

Microplastisphere as a crowded and inclusive micro-ecosystem in seagrass meadow: Cross-kingdom connections and microbial food web - Qiqi Wu; Yu Xia; Yiwei Tao; Chengjun Ge; Yuanyuan Zhao; Dan Feng; Hui Deng (Marine Pollution Bulletin, 2026)

Homogeneous integrated design of polyurethane-based hydrogel electrolytes and electrodes for stretchable supercapacitor - Qingkun Tang; Chengjun Yu; Zuyun Chen; Sisi Yang; Jianxin Tang; Yanqing Li; Songshan Zeng; Xiaoyuan Yu (Chemical Engineering Journal, 2026)

Dark side of biodegradable microplastics in mangrove ecosystem: Plastisphere as an overlooked hotspot of sulfate-reducing metabolism - Yiqiao Zheng; Qiqi Wu; Yu Xia; Hui Deng; Yuanyuan Zhao; Jiwei Luo; Dan Feng; Chengjun Ge (Water Research, 2026)

The photo-release of dissolved organic matter from soil-derived sources: An insight into the impact of acid mine drainage - Lezhang Wei; Fangqing Li; Yu Liu; Qihang Wu; Chengjun Zhang; Xuexia Huang; Dinggui Luo; Juan Liu; Tangfu Xiao (Journal of Environmental Sciences, 2026)

Decadal nutrient addition reveals phosphorus limitation and its adaptive mechanisms in tropical rainforests - Qingshui Yu; Mark A. Anthony; Arthur Gessler; Xiangping Tan; Jiangling Zhu; Chengjun Ji; Zhiyao Tang; Jingyun Fang (Soil Biology and Biochemistry, 2025)

Mitochondria-targeted nanoformulation inhibits periodontal ligament stem cells pyroptosis to promote periodontal tissue regeneration in periodontitis - Xinyuan Shao; Yuxiao Wang; Guichun Wang; Jingjing Hu; Yu Cheng; Chaoqi Wei; Zixuan Shu; Chengjun Peng; Yang Ding; Jian Guo; Zhifei Cheng; Shuangying Gui (Chemical Engineering Journal, 2025)

Synergistic dynamic pitch and incoherent scattering enabling programmable cellulose thermochromic hybrids with UV–Vis-NIR broad modulation and multifunctionality - Binhong Yu; Ziyan Chen; Zhiyuan Sun; Chengjun Yu; Zhenni Lu; Songshan Zeng (Chemical Engineering Journal, 2025)

Comprehensive review on in vitro bioaccessibility of mercury in various foodstuffs - Yu Gong; Chengjun Li; Fei He; Feng Ge; Yongming Ju; Huan Zhong; Weixin Li (Journal of Hazardous Materials, 2025)

Claudin-11 plays a pivotal role in the clathrin-mediated endocytosis of influenza A virus - Xiaofei Yu; Zixin Ni; Yifan Wang; Jingfei Wang; Guohua Deng; Jianzhong Shi; Huihui Kong; Yongping Jiang; Guobin Tian; Chengjun Li; Yoshihiro Kawaoka; Hualan Chen; et al. (Science China Life Sciences, 2025)

Soil-aged microplastics exhibit stronger effects than air- and rainwater-aged ones on the network complexity and assembly process of soil microbial community - Faying Fu; Shu Wang; Xinran Zhang; Yu Xia; Hui Deng; Yuanyuan Zhao; Ying Zhang; Chengjun Ge (Journal of Environmental Chemical Engineering, 2025)

Field Experiments and a Meta‐Analysis Reveal a Minor Influence of Nitrogen Addition on Phosphorus Fractions in Forests - Qingshui Yu; Xiaofeng Ni; Frank Hagedorn; Josep Penuelas; Jordi Sardans; Mai‐He Li; Suhui Ma; Jianxiao Zhu; Di Tian; Chengyang Zheng; Jiangling Zhu; Chengjun Ji; et al. (Global Change Biology, 2025)
Anthropogenic nitrogen (N) inputs can significantly impact nutrient cycling and ecosystem functioning in terrestrial ecosystems. However, the effects of N addition on phosphorus (P) cycling processes in forest ecosystems remain unclear. In this study, we combined data from a long‐term (11‐year) N addition experiment across seven different forests ranging from temperate to tropical biomes, with a global meta‐analysis from 88 relevant publications, to investigate the responses of P cycling‐related variables to N inputs in forest ecosystems. We found that N addition had little effect on most P cycling‐related variables (e.g., leaf P, soil total P, soil available P, soil P fractions, and microbial biomass P) across the studied forest ecosystems. The meta‐analysis highlighted that N‐induced changes in P cycling were highly variable. Only a few variables, such as the leaf P concentration and the activity of soil acid phosphatase, presented significant responses to N addition and changed with climatic zone and the amount and duration of N inputs. Our study suggests that P cycling processes in forest ecosystems remain largely unaffected by N inputs. Our findings contribute to a better understanding and prediction of biogeochemical cycles in the context of N deposition related to anthropogenic activities and global climate change.

Construction of a novel BaZr0.1Ce0.7Y0.2O3-δ-SnO2 heterojunction composite electrolyte for advanced semiconductor ion fuel cells operating at lower temperature down to 350 ℃ - Decai Zhu; Zhongqing Liu; Chengjun Zhu; Yingbo Zhang; Jiangyu Yu; Jiamei Liu; Yuzhao Ouyang; Jie Yu; Nan Wang; Yaohui Niu; Jiali Zhou (Chemical Engineering Journal, 2025)

Determination of alkali metal elements in solid biomass fuel by laser-induced breakdown spectroscopy: Analysis and reduction of chemical matrix effects - Chengjun Li; Zhimin Lu; Jinzheng Chen; Ziyu Yu; Qi Yang; Huaiqing Qin; Xiwen Xing; Qingxiang Ma; Shunchun Yao (Analytica Chimica Acta, 2025)

Deciphering how endogenous mangrove litterfall influences organic matters transformation driven by microbes in sediment with exogenous microplastics inputs - Yu Xia; Shu Wang; Xinran Zhang; Faying Fu; Hui Deng; Yuanyuan Zhao; Huamei Yu; Chengjun Ge (Journal of Hazardous Materials, 2024)

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Precipitation nowcasting leveraging spatial correlation feature extraction and deep spatio-temporal fusion network - Wenbin Yu; Yangsong Li; Cheng Fan; Daoyong Fu; Chengjun Zhang; Yadang Chen; Ming Qian; Jie Liu; Gaoping Liu (Earth Science Informatics, 2024)

Designing of low-temperature high performance semiconductor ionic fuel cells based on molten hydroxide percolation network - Yingbo Zhang; Decai Zhu; Chengjun Zhu; Jiamei Liu; Jiangyu Yu; Zhongqing Liu; Xixi Bai; Nan Wang; Yaohui Niu; Jiali Zhou (Chemical Engineering Journal, 2024)

Mercury supply limits methylmercury production in paddy soils - Huan Zhong; Yao Su; Xinda Wu; Luís Nunes; Chengjun Li; Yunyun Hao; Yu-Rong Liu; Wenli Tang (Science of The Total Environment, 2024)

Identification of organic pollutants and heavy metals in natural rubber wastewater and evaluation its phytotoxicity and cytogenotoxicity - Dayu Zhu; Chengjun Ge; Ying Sun; Huamei Yu; Jun Wang; Hongfei Sun (Chemosphere, 2024)

Distribution, sources and ecological risks of per- and polyfluoroalkyl substances in overlying water and sediment from the mangrove ecosystem in Hainan Island, China - Guoliang Ren; Like Chen; Jinluo Fan; Shuailing Hou; Junnan Chen; Hui Deng; Jiwei Luo; Peng Huang; Yuanyuan Zhao; Jiatong Li; Dan Feng; Chengjun Ge; et al. (Science of The Total Environment, 2024)

Integrated microbiota and multi-omics analysis reveal the differential responses of earthworm to conventional and biodegradable microplastics in soil under biogas slurry irrigation - Yuanyuan Zhao; Huiting Jia; Hui Deng; Chengjun Ge; Wenzhe Xing; Huamei Yu; Jiatong Li (Science of The Total Environment, 2024)

Porous polypyrrole Nanotube-Based Organohydrogels: Versatile materials for robust electromagnetic interference shielding in harsh environments - Lingsai Meng; Shuo Yang; Yu Ma; Yupeng Zou; Yang Zhang; Gang Chen; Chengjun Dong; Hongtao Guan (Chemical Engineering Journal, 2024)

Preparation of leaf protoplasts from Populus (Populus × xiaohei T. S. Hwang et Liang) and establishment of transient expression system - Chengjun Yang; Ruiqiang Yu; Jinbo Li; Kai Wang; Guanjun Liu (Journal of Plant Physiology, 2023)

Characteristics of vertical distributions of methane and dimethylsulphoniopropionate in the southern Yap Trench - Yuhuan Huang; Chengjun Sun; Lina Lü; Neal Xiangyu Ding; Liangmin Yu; Guipeng Yang; Haibing Ding (Journal of Oceanology and Limnology, 2023)

Integrated microbiome and multi-omics analysis reveal the molecular mechanisms of Eisenia fetida in response to biochar-derived dissolved and particulate matters - Huiting Jia; Yuanyuan Zhao; Hui Deng; Huamei Yu; Chengjun Ge; Jiatong Li (Journal of Hazardous Materials, 2023)

Convergence of soil bacterial communities with time and reduction of bacterial interaction complexity in response to meso- and microplastic stress - Lin Yue; Yangbo Liu; Guanhui Li; Hui Deng; Yuanyuan Zhao; Dan Feng; Hongfei Sun; Huamei Yu; Chengjun Ge; Haiying Chen (Journal of Environmental Chemical Engineering, 2023)

Wnt10a downregulation contributes to MEHP-induced disruption of self-renewal and differentiation balance and proliferation inhibition in GC-1 cells: Insights from multiple transcriptomic profiling - Yifan Hong; Xiazhu Zhou; Qi Li; Jing Chen; Yuexin Wei; Siyuan Wang; Xiangqin Zheng; Jie Zhao; Chengjun Yu; Jun Pei; Jie Zhang; Chunlan Long; et al. (Environmental Pollution, 2023)

Benefited wastewater utilization via configurable, spatialized, and microorganisms-integrated biophotonic systems - Yantong Liu; Longfei Chen; Le Yu; Jiaomeng Zhu; Fang Wang; Fenghua Jiang; Chengjun Sun; Li Zheng; Yi Yang (Chemical Engineering Journal, 2023)

Mangrove degradation retarded microplastics weathering and affected metabolic activities of microplastics-associated microbes - Hui Deng; Yuqing Zhang; Dazhen Li; Qianqian Fu; Jianxiong He; Yuanyuan Zhao; Dan Feng; Huamei Yu; Chengjun Ge (Journal of Hazardous Materials, 2023)

Response of earthworms to microplastics in soil under biogas slurry irrigation: Toxicity comparison of conventional and biodegradable microplastics - Yuanyuan Zhao; Huiting Jia; Hui Deng; Wenzhe Xing; Dan Feng; Jiatong Li; Chengjun Ge; Huamei Yu; Ying Zhang; Haiying Chen (Science of The Total Environment, 2023)

Multiple-functionalized biochar affects rice yield and quality via regulating arsenic and lead redistribution and bacterial community structure in soils under different hydrological conditions - Xing Yang; Zhinan Dai; Chengjun Ge; Huamei Yu; Nanthi Bolan; Daniel C.W. Tsang; Hocheol Song; Deyi Hou; Sabry M. Shaheen; Hailong Wang; Jörg Rinklebe (Journal of Hazardous Materials, 2023)

Iron-modified phosphorus- and silicon-based biochars exhibited various influences on arsenic, cadmium, and lead accumulation in rice and enzyme activities in a paddy soil - Xing Yang; Ergang Wen; Chengjun Ge; Ali El-Naggar; Huamei Yu; Shengsen Wang; Eilhann E. Kwon; Hocheol Song; Sabry M. Shaheen; Hailong Wang; Jörg Rinklebe (Journal of Hazardous Materials, 2023)

Reconfigurable modular microbiota systems for efficient and sustainable water treatment - Longfei Chen; Yantong Liu; Pengfu Tian; Le Yu; Fang Wang; Hongshan Xu; Yifan Wang; Wei Li; Li Zheng; Fenghua Jiang; Chengjun Sun; Xuming Zhang; et al. (Chemical Engineering Journal, 2023)

Flow pattern transition and wave characteristics of impinging jet flow on a spinning disk reactor - Dongxiang Wang; Chengjun Gu; Cheng Sun; Xiang Ling; Hao Peng; Xinjun Yang; Fangyang Yuan; Jiyun Du; Wei Yu (Chemical Engineering Journal, 2023)

New insights into the toxic interactions of polyvinyl chloride microplastics with bovine serum albumin - Peng Ju; Yu Zhang; Jinfeng Ding; Yifan Zheng; Shuai Wang; Fenghua Jiang; Chengjun Sun (Environmental Science and Pollution Research, 2021)

Photolysis of bis(2-ethylhexyl) phthalate in aqueous solutions at the presence of natural water photoreactive constituents under simulated sunlight irradiation - Qian Yu; Xiyao Xiong; Jun He; Yuegang Zuo; Yong Chen; Chengjun Wang (Environmental Science and Pollution Research, 2019)

Degradation potential and diversity of oil-degrading bacteria isolated from the sediments of the Jiaozhou Bay, China - Wei Gao; Xiangxing Gao; Tiezhu Mi; Bin Han; Yiran Zhang; Xinzi Li; Xiaofei Yin; Chengjun Sun; Qian Li; Zhisong Cui; Xiao Luan; Zhigang Yu; et al. (Acta Oceanologica Sinica, 2019)

A generalized theory of the figure of the Earth: on the global dynamical flattening - Chengjun Liu; Chengli Huang; Yu Liu; Mian Zhang (Journal of Geodesy, 2019)

A generalized theory of the figure of the Earth: formulae - Chengli Huang; Yu Liu; Chengjun Liu; Mian Zhang (Journal of Geodesy, 2019)

Removal of tetracyclines, sulfonamides, and quinolones by industrial-scale composting and anaerobic digestion processes - Hang Liu; Chengjun Pu; Xiaolu Yu; Ying Sun; Junhao Chen (Environmental Science and Pollution Research, 2018)

Methodology for antibody preparation and detection of southern rice black-streaked dwarf virus - Zhuo Chen; Chengjun Yin; Jiaju Liu; Mengjiao Zeng; Zhenchao Wang; Dandan Yu; Liang Bi; Linhong Jin; Song Yang; Baoan Song (Archives of Virology, 2012)

Protective effects of Lycium barbarum polysaccharide on neonatal rat primary cultured hippocampal neurons injured by oxygen-glucose deprivation and reperfusion - Chen Rui; Li Yuxiang; Hao Yinju; Zhu Qingluan; Wu Yang; Zhao Qipeng; Wang Hao; Ma Lin; Liu Juan; Zhao Chengjun; Jiang Yuanxu; Wang Yanrong; et al. (Journal of Molecular Histology, 2012)

Debris flow and landslide hazard mapping and risk analysis in China - Xilin Liu; Chengjun Yu; Peijun Shi; Weihua Fang (Frontiers of Earth Science, 2012)

Comparison of sociability, parental care and central estrogen receptor alpha expression between two populations of mandarin voles (Microtus mandarinus) - Ruiyong Wu; Aifang Yuan; Qinwei Yuan; Rui Guo; Fadao Tai; Zhenzhen Song; Chengjun Yu (Journal of Comparative Physiology A, 2011)

Membrane dielectric responses of bufalin-induced apoptosis in HL-60 cells detected by an electrorotation chip - Chengjun Huang; Ailiang Chen; Min Guo; Jun Yu (Biotechnology Letters, 2007)

Characterization of An Avian Influenza Virus of Subtype H7N2 Isolated from Chickens in Northern China - Yanbing Li; Chengjun Li; Liling Liu; Hongwei Wang; Chuanbin Wang; Guobing Tian; Robert G. Webster; Kangzhen Yu; Hualan Chen (Virus Genes, 2006)

Antidepressant-like effects of PDE4 inhibitors mediated by the high-affinity rolipram binding state (HARBS) of the phosphodiesterase-4 enzyme (PDE4) in rats - Han-Ting Zhang; Yu Zhao; Ying Huang; Chengjun Deng; Allen T. Hopper; Michael De Vivo; Gregory M. Rose; James M. O’Donnell (Psychopharmacology, 2006)